PREPARATION OF E-ALPHA-ARYLIDENE-GAMMA-BUTYROLACTONES AND Z-ALPHA-ARYLIDENE-GAMMA-BUTYROLACTONES FROM Z-ALPHA-STANNYLMETHYLENE-GAMMA-BUTYROLACTONES - STEREOSELECTIVE SYNTHESIS OF (+/-)-SAVININ AND (+/-)-GADAIN - LEE, E; HUR, CU; JEONG, YC; RHEE, YH; CHANG, MH (ROYAL SOC CHEMISTRY, 1991)
E-alpha-Arylidene-gamma-butyrolactones were prepared by the radical addition-elimination reaction of Z-alpha-stannylmethylene-gamma-butyrolactones, whereas the palladium(0) catalysed cross-coupling reaction of the same substrates afforded Z-alpha-arylidene-gamma-butyrolactones.
Keywords: CYCLIZATION; ELIMINATION; ARYLATION